2007
DOI: 10.1897/06-560
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of freshwater mussel toxicity data in the derivation of water quality guidance and standards for copper

Abstract: The state of Oklahoma has designated several areas as freshwater mussel sanctuaries in an attempt to provide freshwater mussel species a degree of protection and to facilitate their reproduction. We evaluated the protection afforded freshwater mussels by the U.S. Environmental Protection Agency (U.S. EPA) hardness‐based 1996 ambient copper water quality criteria, the 2007 U.S. EPA water quality criteria based on the biotic ligand model and the 2005 state of Oklahoma copper water quality standards. Both the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 12 publications
2
38
1
Order By: Relevance
“…March et al [8] compiled freshwater mussel data from highquality toxicity tests. Among the data, acute 96-h copper EC50s for newly transformed juveniles of eight mussel species Fig.…”
Section: Toxicity Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…March et al [8] compiled freshwater mussel data from highquality toxicity tests. Among the data, acute 96-h copper EC50s for newly transformed juveniles of eight mussel species Fig.…”
Section: Toxicity Modelingmentioning
confidence: 99%
“…Specifically, the median effective concentrations (EC50s) for mussels were 30 to 75% below the final acute values used to derive the U.S. Environmental Protection Agency (U.S. EPA) hardness-dependent acute water quality criterion (WQC) for copper [7]. In addition, March et al [8] calculated 14 mussel genus mean acute values (GMAVs) for copper and found that when including mussel data in the database used to derive the hardness-dependent WQC for copper [7], GMAVs for mussels accounted for the first three lowest values or 10 of the 15 lowest values.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, mussels are generally underrepresented in toxicity databases used for the development of water quality criteria, standards, and other environmental guidance values [6,7,12,13]. In addition, the limited mussel data available have been generated mostly from toxicity tests with a few species of the taxonomic tribe Lampsilini [5][6][7][8][9][10][11][12][13][14][15][16]. Studies with broader phylogenetic representation are needed to understand the range of sensitivity among freshwater mussels, compare the overall sensitivity of mussels to other freshwater species, and evaluate the degree to which existing or proposed environmental guidance values are protective of mussels.…”
Section: Introductionmentioning
confidence: 99%